Effect of Preoperative Atrial Fibrillation on Postoperative Outcome following Cardiac Surgery. (30th July 2012) - Al-Sarraf, Nael; Thalib, Lukman; Hughes, Anne; Tolan, Michael; Young, Vincent; McGovern, Eillish
Abstract : Atrial fibrillation remains the commonest arrhythmia encountered in cardiac surgery. Data on the effect of preoperative atrial fibrillation on postoperative outcome remain limited. We sought to assess the effects preoperative atrial fibrillation on patients' outcome following cardiac surgery. This is a retrospective review of prospectively collected departmental data of all patients who underwent cardiac surgery over 8-year period. Our cohort consisted of 3777 consecutive patients divided into atrial fibrillation (n = 413, 11%) and sinus rhythm (n = 3364, 89%). Postoperative complications and in-hospital mortality were analysed. Univariate analysis showed significantly increased mortality and major complications in atrial fibrillation compared to sinus rhythm patients. Using multiple logistic regression analysis and after accounting for Euro SCORE as a confounding variable, we found that preoperative atrial fibrillation significantly increases the risk of mortality (OR 1.7), low cardiac output state (OR 1.3), prolonged ventilation (OR 1.4), infective complication (OR 1.5), gastrointestinal complications (OR 2.0), and intensive care unit readmission (OR 1.6). Preoperative atrial fibrillation in cardiac surgery patients increases their risk of mortality and major complications following cardiac surgery. Surgical strategies such as Cox-Maze procedure may be beneficial in these patients.